2021
DOI: 10.1016/j.jbc.2021.100419
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate is essential for thymus growth

Abstract: Thymus organogenesis and T cell development are coordinated by various soluble and cell-bound molecules. Heparan sulfate (HS) proteoglycans can interact with and immobilize many soluble mediators, creating fields or gradients of secreted ligands. While the role of HS in the development of many organs has been studied extensively, little is known about its function in the thymus. Here, we examined the distribution of HS in the thymus and the effect of its absence on thymus organogenesis and T cell development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“… 137 , 138 Cell‐surface binding of CCL21 is mediated by the heparan sulfate strongly expressed by these cells, and consistent with this, the EXT family genes, Ext1 and Ext2 , that encode the glycosyl transferases for heparan sulfate biosynthesis are highly expressed in mFbs and pericytes. 138 James et al reported that CCL21 captured by the blood‐vessel surrounding fibroblasts and pericytes promotes T cell emigration from the neonatal mouse thymus, suggesting a synergy between TEC‐dependent production and mesenchymal cell‐dependent immobilization of chemokines for controlling T cell migration. 137 A study by Hsu et al demonstrated that elimination of heparan sulfate in the thymus by genetic deletion of Ext1 resulted in a marked decrease in the number of thymic fibroblasts and TECs as well as thymocytes.…”
Section: The Medullary Fibroblast (Mfb)supporting
confidence: 58%
See 4 more Smart Citations
“… 137 , 138 Cell‐surface binding of CCL21 is mediated by the heparan sulfate strongly expressed by these cells, and consistent with this, the EXT family genes, Ext1 and Ext2 , that encode the glycosyl transferases for heparan sulfate biosynthesis are highly expressed in mFbs and pericytes. 138 James et al reported that CCL21 captured by the blood‐vessel surrounding fibroblasts and pericytes promotes T cell emigration from the neonatal mouse thymus, suggesting a synergy between TEC‐dependent production and mesenchymal cell‐dependent immobilization of chemokines for controlling T cell migration. 137 A study by Hsu et al demonstrated that elimination of heparan sulfate in the thymus by genetic deletion of Ext1 resulted in a marked decrease in the number of thymic fibroblasts and TECs as well as thymocytes.…”
Section: The Medullary Fibroblast (Mfb)supporting
confidence: 58%
“…Two very recent reports demonstrated that CCL21 is displayed on the surface of mFbs and pericytes around blood vessels 137,138 . Cell‐surface binding of CCL21 is mediated by the heparan sulfate strongly expressed by these cells, and consistent with this, the EXT family genes, Ext1 and Ext2 , that encode the glycosyl transferases for heparan sulfate biosynthesis are highly expressed in mFbs and pericytes 138 . James et al reported that CCL21 captured by the blood‐vessel surrounding fibroblasts and pericytes promotes T cell emigration from the neonatal mouse thymus, suggesting a synergy between TEC‐dependent production and mesenchymal cell‐dependent immobilization of chemokines for controlling T cell migration 137 .…”
Section: The Medullary Fibroblast (Mfb)mentioning
confidence: 64%
See 3 more Smart Citations